Daily practice in guideline adherence to adjuvant chemotherapy in stage III colon cancer and predictors of outcome. Issue 8 (August 2021) - van den Berg, I.; van de Weerd, S.; van Klaveren, D.; Coebergh van den Braak, R.R.J.; van Krieken, J.H.J.M.; Koopman, M.; Roodhart, J.M.L.; Medema, J.P.; IJzermans, J.N.M.
Abstract: Introduction: Although guidelines recommend adjuvant chemotherapy for stage III colon cancer patients, many patients do not receive adjuvant chemotherapy. The aim of this study was to identify reasons for guideline non-adherence and assess the effect on patient outcomes in a multicenter cohort of stage III colon cancer patients who received surgery plus adjuvant chemotherapy or surgery alone. Methods: Patients who underwent surgery between 2007 and 2017 were included. Reasons for non-adherence were determined. Propensity score analyses with inverse probability weighting were performed to adjust for confounding factors. Cox proportional hazards regression and risk stratified analyses were performed to assess the association of guideline adherence and other potential predictors with recurrence free survival (RFS). Results: Data of 575 patients were included of whom 61% received adjuvant chemotherapy. In 87 of 222 patients (39%) who did not receive adjuvant chemotherapy, no reason was documented. Only age was predictive for receiving chemotherapy. Patients who received adjuvant chemotherapy had longer RFS (HR 0.42, 95%CI 0.29–0.62, p < 0.001). High T- and N-stage were associated with poorer RFS HR 2.0 (95%CI 1.58–2.71, p < 0.001) and HR 2.19 (95%CI 1.60–2.99, p < 0.001) respectively. Risk groups were identified with distinct prognosis and treatment effect and a nomogram is presented to visualize individualized RFS differences. Conclusion: This study shows considerable variation in guideline adherence to adjuvant chemotherapy and poor documentation on reasons for non-adherence. Optimizing adherence and gaining insight in reasons for non-adherence is advocated as this can lead to significant RFS benefit, especially in patients with high T-and N-stage tumors.